WSN and IoT an integrated approach for smart applications - Rani, Shalli; Taneja, Ashu (CRC Press, 2024)
"This book discusses the integration of IoT and WSN which enables an efficient communication flow between sensor nodes and wireless terminals and covers the role of ML, AI, deep learning, and blockchain technologies which gives way to intelligent networks. A wide range of communication paradigms pertaining to smart cities, including smart healthcare, smart transportation, and intelligent data processing are covered, making this the perfect read for academicians, researchers, advanced-level students, and engineers who are interested in the advancements of IoT and WSN for varied applications of smart cities including smart healthcare, smart vehicles, and smart homes"--
Includes bibliographical references. - Description based on print version record and CIP data provided by publisher; resource not viewed
Keywords: Internet of things; Wireless sensor networks; Internet des objets; Réseaux de capteurs sans fil